Everything You Always Wanted to Know About Salmonella Type 1 Fimbriae, but Were Afraid to Ask - Kolenda, Rafal; Ugorski, Maciej; Grzymajlo, Krzysztof (Frontiers in Microbiology, 2019)
Initial attachment to host intestinal mucosa after oral infection is one of the most important stages during bacterial pathogenesis. Adhesive structures, widely present on the bacterial surface, are mainly responsible for the first contact with host cells and stabilisation of host-pathogen interactions. Among dozens of different bacterial adhesins, type 1 fimbriae (T1F) are one of the most common adhesive organelles in the members of the Enterobacteriaceae family, including Salmonella spp., and are important virulence factors in pathogenicity. Those long, thin structures, composed mainly of FimA proteins, are responsible for recognising and binding high-mannose oligosaccharides, which are carried by various glycoproteins and expressed at the host cell surface, via FimH adhesin, which is presented at the top of T1F. In this review, we discuss investigations into the functions of T1F, from the earliest work published in 1958 to operon organization, organelle structure, T1F biogenesis, and the various functions of T1F in Salmonella-host interactions. We give special attention to regulation of T1F expression and their role in binding of Salmonella to cells, cell lines, organ explants, and other surfaces with emphasis on biofilm formation, and discuss T1F role as virulence factors based on work using animal models. We also discuss the importance of allelic variation in fimH to Salmonella pathogenesis, as well as role of FimH in Salmonella host specificity.